PERMASALAHAN NON-REVENUE WATER (NRW) DALAM PELAYANAN AIR BERSIH - Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
The growth of population need more water. Public water utilities(PAM) have to anticipate the new demand by increase the capacity. However, the rise of capacity and production are not the single way to solve increasing of demand. Combining the increasing of capacity and Non-revenue water (NRW) reduction is better than the single approach. Currently, most of the PAM has very high NRW. Many of them have NRW equivalent to the half of production. More family will be served if NRW reduction success. Furthermore, the income of PAM also will up and cost of production as well as cost of investment will down On the other hand, water resources will used efficiently. Increasing of capacity will be required if NRW reduction have been done maximally but still not sufficient for all demand.